Study of the Lubricating Ability of Protic Ionic Liquid on an Aluminum–Steel Contact - Akshar Patel; Hong Guo; Patricia Iglesias (Lubricants, 2018)
Contact friction between moving components leads to severe wear and failure of engineering parts, resulting in large economic losses. The lubricating ability of the protic ionic liquid, tri-[bis(2-hydroxyethylammonium)] citrate (DCi), was studied as a neat lubricant and as an additive in a mineral oil (MO) at various sliding velocities and constant load on an aluminum–steel contact using a pin-on-disk tribometer. Tribological tests were also performed at different concentrations of DCi. When DCi was used as an additive in MO, friction coefficient and wear volume were reduced for each sliding velocity, with a maximum friction and wear reduction of 16% and 40%, respectively, when 2 wt % DCi was added to MO at a sliding velocity of 0.15 m/s. Scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX) were also applied to analyze the wear mechanism of the interface lubricated by MO and DCi as additive.